The World Bank Research Program 2002-2003 : Abstracts of Current Studies - World Bank (The World Bank, 2004)
The World Bank's research program has four basic objectives: to broaden the understanding of development, to assist in developing research capacity in the Bank's member countries, to improve its capacity to advise its members, and to support all aspects of its own operations. Whether these aims are achieved depends in part on how extensively Bank research is used internally and externally. In early 2004, surveys were commissioned to assess the use of publications including Bank-wide research (annual flagship publications, Policy Research Reports, Policy Research Working Papers, and the two research journals) by Bank staff and by the Bank's clients. The findings lead to four main conclusions: clients use Bank research publications frequently, Bank research publications are influential, translations are important, and for external clients the Internet is an important source of information. The World Bank Research Program reports on research projects that were initiated, under way, or completed from July 2001 through June 2003 and, for the first time, it includes summaries of large research programs. These multiyear programs undertake analysis on several broad development related issues with the aim of providing strategic directions on critical problems facing Bank clients and operations. Each program centers on a theme giving coherence to the research and its outputs. This title addresses thematic programs such as investment climate, rural development, finance and trade